2023
DOI: 10.1186/s12872-023-03052-x
|View full text |Cite
|
Sign up to set email alerts
|

Automated 4D flow cardiac MRI pipeline to derive peak mitral inflow diastolic velocities using short-axis cine stack: two centre validation study against echocardiographic pulse-wave doppler

Abstract: Background Measurement of peak velocities is important in the evaluation of heart failure. This study compared the performance of automated 4D flow cardiac MRI (CMR) with traditional transthoracic Doppler echocardiography (TTE) for the measurement of mitral inflow peak diastolic velocities. Methods Patients with Doppler echocardiography and 4D flow cardiac magnetic resonance data were included retrospectively. An established automated technique was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This indicates that both echoPIV and 4D flow MRI are similarly biased towards lower velocities than pulsed-wave Doppler. In addition, research comparing 4D flow MRI with traditional transthoracic pulse-wave Doppler echocardiography for the measurement of mitral inflow peak diastolic velocities reported that MRI underestimated peak diastolic velocities by 0.05 m/s (95% CI -0.37 to 0.46 m/s)[24]. Thus, the differences between echoPIV and 4D-flow MRI found in this study are comparable with previous inter-modality studies.…”
Section: Discussionsupporting
confidence: 85%
“…This indicates that both echoPIV and 4D flow MRI are similarly biased towards lower velocities than pulsed-wave Doppler. In addition, research comparing 4D flow MRI with traditional transthoracic pulse-wave Doppler echocardiography for the measurement of mitral inflow peak diastolic velocities reported that MRI underestimated peak diastolic velocities by 0.05 m/s (95% CI -0.37 to 0.46 m/s)[24]. Thus, the differences between echoPIV and 4D-flow MRI found in this study are comparable with previous inter-modality studies.…”
Section: Discussionsupporting
confidence: 85%
“…CMR can assess the rapid myocardial velocities (e’) analogous with echocardiography Tissue Doppler Imaging with similar levels of agreement and have similar limitations as phase-contrast CMR, limited by temporal resolution and evidence base [ 74 , 75 ]. 4D-CMR shows promise as an alternative method of CMR diastolic assessment [ 76 ]; however, it requires long acquisition, specialist postprocessing, and therefore is not in routine clinical use and limited to research centres.…”
Section: Introductionmentioning
confidence: 99%